Aortic root thrombus causing non-ST elevation myocardial infarction after left ventricular assist device. (July 2023) - Kallur, Akhil S; Bien-Aime, Fred; Sallam, Tariq; Jawaid, Yasir; Zaaqoq, Akram M
A 61-year-old male presented with a history of ischemic cardiomyopathy requiring left ventricular assist device (LVAD) implantation 9 months prior to presentation. The patient was on aspirin and warfarin as part of his LVAD management. The patient had chest pain and was found to have non-ST elevation myocardial infarction. Despite being on warfarin, a subtherapeutic international normalized ratio of 1.6 was measured on admission. Lactate dehydrogenase was 694 U/L (12–146) and high-sensitivity troponin peaked at 47, 093 ng/L. Left heart catheterization revealed an extensive aortic root thrombus (AT). AT is an uncommon cause of thromboembolic events in long-term LVAD patients. Thrombotic events in LVAD patients are pump thrombosis, cerebrovascular accidents, heparin-induced thrombocytopenia, and rarely, AT. There is no well-described management of such a rare complication. In our report, we suggest a multidisciplinary approach and consideration of conservative treatment of these patients.